PENJERNIHAN MINYAK JELANTAH MENJADI LILIN AROMATIK PALMAROSA DAN LEMON SEBAGAI PENCEGAHAN DBD - Utami, Nastiti; Lindawati, Novena Yety; Pramesti, Erika Diyah; Sari, Fitri Atrika; Chotimah, Intan Kusnul; Widya, Selsa Rizky; Alifya, Zhausan Dina (Universitas AMIKOM Yogyakarta, 2023)
This community service was held on January 21, 2023 at the Inclusion Studio (Anugerah Aulia) Cemani Village, Grogol District, Sukoharjo Regency with 30 participants. This community service was carried out through 3 stages, the preparation stage, the implementation stage, and the evaluation stage. The purpose of this activity is to increase public knowledge about the prevention of dengue hemorrhagic fever by utilizing aromatik candles as mosquito repellents and motivating the community by using used cooking oil to create new businesses as an increase in micro, small and medium enterprises in Cemani Village. This activity was successful by obtaining an average pretest score of 44.58%, after counseling and workshops, community knowledge increased with an average posttest score of 90.83%.